Marginalisation in education systems: The Programme for International Student Assessment (PISA) and the failure discourse around the Italian education system - de Freitas, Rogério Gonçalves; Chaves, Vera Lucia Jacob; Nozaki, Hajime Takeuchi (Education Policy Analysis Archives, 2019)
The Organisation for Economic Cooperation Development (OECD) created the Programme for International Student Assessment (PISA) as a political actor in global education through a logic of governance by numbers (Grek, 2009). This article discusses how PISA has became a major showcase for the OECD as an assessment tool par excellence while also producing marginalisation discourses. By approaching neoliberal globalisation and its aim at restoring the transnational capitalist class’ power over the “dangerous” classes (Harvey, 2005; Holman, 2006; Van Apeldoorn, 2001; Van der Pijl, 2010), this article analyses how school privatisation has grown in the Italian system over the last few years in the face of the PISA discourse (Bertozzi & Graziano, 2004). Building on document research and reports by Italian teachers, it traces how PISA’s pressure over the Italian school system has produced a twofold marginalizing effect. The first effect is the periodical disclosure of PISA rankings to distinguish successful from failed education systems. In fact, recent PISA results have placed the Italian system as a failed, technologically retarded system compared to those of high-performance countries. The second effect is the burst of neoliberal feelings among teachers, who report both stigma and guilt.